Revenge: Meghan, Harry, and the War Between the Windsors - Bower, Tom (New York : Atria Books, 2022)
"Reveals the inside story about Meghan Markles journey from minor actress and attempted activist to the woman powerful enough to drive a wedge within the British Royal Family"--
Keywords: Meghan, -- Duchess of Sussex, -- 1981-; Harry, -- Prince, Duke of Sussex, -- 1984-; Monarchy -- Great Britain; History -- 20th century; Princes -- Great Britain; Biography; Princesses -- Great Britain; Biography; Royal couples -- Great Britain; Biographies